Proposed New Business Model and Transformation Strategy For CV Fruity Indonesia - Musbar, Febrina Piecella; Nasution, Reza Ashari (The Indonesian Journal of Business Administration, 2014)
Abstract—Beverage Industry as one of the largest contributors to creative industry is changing continually. New competitors are emerging and current competitors are increasing their competitive advantage. CV Fruity Indonesia as one of the pioneer in juice retailing business in Bandung needs to identify new business model and transform its business to keep up with current environment and competition and also to prepare for the future. The purpose of this research is to provide new business model and transformation strategy for CV Fruity Indonesia that will increase its competitive advantage. In this research, existing business models of the company is analyzed using nine building blocks of Business Model Canvas while the beverage industry will be analyzed using Six Paths Framework tool from Blue Ocean Strategy. The research finds that there are three main additions to the business model that should be implemented and integrated with company’s existing business models, business model counter and mini cafe. The new proposed business models’ competitive advantage then analyzed using competitive positioning analysis against the current strategic groups within the industry. The new business models are implemented using business transformation strategy, which consists of 2 phases. The first phase is Operating Excellence and the second phase is Business Enhancement. The implementation plan expanded to eight months period so that the company could prepare the needed resources before fully transform its business models. Keywords: Business Model, Business Transformation, Beverage Industry, Blue Ocean Strategy, Six Paths Framework